PENERAPAN MODEL PEMBELAJARAN SCRAMBLE TERHADAP HASIL BELAJAR KOGNITIF SISWA - Hikmah, Darul; Hadi, Wiwin Puspita; Sidik, Rahmad Fajar; Qomaria, Nur; Yasir, Mochammad (Natural Science Education Research, 2023)
This study aims to determine the results of student cognitive learning after the application of Scramble learning model. The method used is the pre-experimental type of quantitiative method with the One Group Preterest-Posttest Design design. The sample in this study ware students class VII A MTS Raudlatul Ulum Klampis amounted to 19 students of the third semester of 2021/2022. Data-up technique through cognitive learning outcomes test. The average value of the preterest value is 48.42, while the average value of the posttest value is 84.11. Based on the results of hypothesis testing, the pretest and posttest 0,000 equal or less than 0,05. Then the avarage N-gain valuenof cognitive learning is 0,73 with high criteria.